NEW RAW MATERIALS RECOMMENDED FOR USE IN CEMENT PLANTS OF KARAKALPAKSTAN - Kudaibergenova, A.M.; Orazimbetova, G.Z.; Turdimuratov, M.M. (FAN va JAMIYAT, 2023)
It is presented the results of the study of the chemical composition of technological samples of limestone "Dusshebulak", gabbroic rock "Sheikhdjelil", dune sand deposit "Muynak" and brown iron rock "Hujakul" to determine their compliance with the requirements of O’z DSt 2950:2015 "Raw materials for the production of portland cement clinker. Technical conditions" to the chemical composition of carbonate, aluminosilicate raw materials and eruptive rocks used in the production of portland cement clinker.